A TALE OF TWO LATIN AMERICAN COUNTRIES: THE DEMOCRATIC RULE OF LAW IN MEXICO AND URUGUAY - Bardallo Bandera, Joaquín (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2015)
Why is the democratic rule of law stronger in Uruguay than in Mexico? This work focuses on the state of the democratic rule of law in these countries by conducting a most similar systems comparison. The premise of this work is that there is a gap in the literature on factors that have historically made Uruguay the country with the strongest democratic rule of law in Latin America, and Mexico the one with the weakest democratic rule of law. Historical institutionalism is used to see how the sequence of political regimes, as well as the evolution of civil-military relations in the two countries, may explain the divergent outcomes. Emphasizing path dependency, this analysis is conducted using a methodology of process tracing. This research serves to put forward propositions in the form of a testable hypothesis on the causes that have led Mexico and Uruguay down different paths in relation to the rule of law. It also serves to fill a gap in the literature as cross-national differences on rule of law in Latin America have not been sufficiently well explained.